The rising of “Modern Actinobacteria” era - Law, Jodi Woan-Fei; Letchumanan, Vengadesh; Tan, Loh Teng-Hern; Ser, Hooi-Leng; Goh, Bey-Hing; Lee, Learn-Han (Progress In Microbes & Molecular Biology, 2020)
The term “Modern Actinobacteria” (MOD-ACTINO) was coined by a Malaysian Scientist Dr. Lee Learn-Han, who has great expertise and experience in the field of actinobacteria research. MOD-ACTINO is defined as a group of actinobacteria capable of producing compounds that can be explored for modern applications such as development of new drugs and cosmeceutics. MOD-ACTINO members consist of already identified or novel actinobacteria isolated from special environments: mangrove, desert, lake, hot spring, cave, mountain, Arctic and Antarctic regions. These actinobac-teria are valuable sources for various industries which can contribute directly/indirectly towards the improvement in many aspects of our lives.